Board reforms and firm value: Worldwide evidence - Fauver, Larry; Hung, Mingyi; Li, Xi; Taboada, Alvaro G. (Journal of Financial Economics, 2017)
We examine the impact of corporate board reforms on firm value in 41 countries. Using a difference-in-differences design, we find that board reforms increase firm value. Reforms involving board and audit committee independence, but not reforms involving separation of chairman and chief executive officer positions, drive the valuation increases. In addition, while comply-or-explain reforms result in a greater increase in firm value than rule-based reforms, the effects of reforms are similar across civil law and common law countries. Further investigation shows that the subsequent change in board independence plays an important role in explaining the effectiveness of the reforms.